PENGARUH PERUBAHAN STATUS, EMPLOYEE ENGAGEMENT, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS PELAPORAN KEUANGAN - Nani Yuheti Yuniatin; Noer Azam Achsani; Hendro Sasongko (EKUITAS (Jurnal Ekonomi dan Keuangan), 2015)
This study aimed to examine the effect of changes in status, employee engagement, and the utilization of information technology on the quality of financial reporting. Analysis of variance (ANOVA) was used to examine changes in the status of Bogor Agricultural University. Moreover we employ a multiple regression analysis to examine the effect of employee engagement and information technology in performance financial of report.  In addition, Ultrecht Work Engagement Scale (UWES) was used to examine the financial human resource mapping. The results of ANOVA test showed that there was no significant difference of the financial management of Bogor Agricultural University before and after the implementation of Public Service Board (BLU). Furthermore, multiple linear regression test results showed that the factors that affect the performance of financial reports are employee engagement and use of information technology. However, it is found that the factor that really affects the performace of financial reports is the use of information technology. Finally, the test results of the mapping showed that employee engagement of human resources staff of Bogor Agricultural University are in medium position indicating that it needs to be maintained and improved